Pengayaan Lomba Pada Bulan Muharram Untuk Membentuk Generasi Muda Yang Cerdas, Sholih Dan Berprestasi Di Desa Margamulya Kecamatan Pangalengan Kabupaten Bandung - Santika, Nisa; Nurlatifah, Ilva; Noor, Firman Maulana (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Children’s knowledge about the Islamic religion is taught very minimally, besides that their attention to religion can also be influenced by the environment around them. One of the aims of this research is to introduce children to major celebrations in Islam, especially the Islamic New Year celebration, which perhaps not all children know about. ApaRT from that, it also aims to provide an in-depth understanding and increase children’s religious knowledge. This research uses the Sisdamas method or is based on community empowerment regarding the problems, advantages and needs of the community. The approach used is to use an educational science perspective, especially focusing on religious knowledge in TPAs and Islamic boarding schools. The results of this research show that the Muharram competition activities had a significant effect in that children became more enthusiastic and motivated in studying Islam.